How we repair acute type A dissection in Gangnam severance hospital. (January 2023) - Kim, Chong Hoon; Song, Suk-Won
Total arch replacement for aortic dissection is traditionally associated with high mortality and morbidity rates. Here, we share our strategies for improving surgical outcomes such as Y incision, unilateral antegrade cerebral perfusion, Teflon felt neo-media formation, and reinforcement of the anastomosis site.